PROGRAM KPPK DI KEUSKUPAN RUTENG SEBAGAI UPAYA MENINGKATKAN KESADARAN PASUTRI AKAN HAKIKAT PERKAWINAN KATOLIK - Yohanes S. Lon (Unika Santu Paulus Ruteng, 2020)
For Catholics, marriage is a divine calling of God. Marriage is one of the seven sacraments within the Church. It is the symbol of the God’s salvation. Through marriage a husband and a wife can experience the salvation of God. Both of them also has functioned to reveal the God’s grace, salvation and blessings for each other. The Catholic Church also consider a family as a a mini or small church. A mommitment to marry in Catholic ways is beautiful but not an easy decision. A couple may face challenges and problems. In order to increase of the couples’ understanding of Catholic Marriage and to strengthen them to cope with various marrietal problems, the Local Catholic Church of Ruteng Diocese provides an Course on Preparation of Catholic Marriage to the future couples who want to marry in Catholic Church. This articles aims at describing on how the program is planned, implemented and the expected result after joinging the course. This program is a way to educate and to rise the awareness of the couple about the Catholic marriage. It is considered useful. However, it would be better if it is run in more professional way. Moreover, this program should be added with continous other activities such as pastoral of marriage and marriage counceling. It is also an urgent to have marriage crisis centre that helps the couples who have problems of marriage.